Zawarcie umowy o udział w imprezie turystycznej według ustawy o imprezach turystycznych i powiązanych usługach turystycznych - Mielniczuk, Martyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The entry into force of the Act on package travel and linked travel arrangements implementing Directive 2015/2302 has triggered a small revolution in the activities of organisers and other traders. This article analyzes the provisions of the new act regarding the conclusion of the package travel contract, including information obligations of an organizer and a retailer, which they must fulfill before concluding a contract. Special attention was also paid to changes regarding the definition of the subject of the package travel contract and contracting parties
Keywords: tourist event; contract for participation in a tourist event; tour operator; traveler; signing an agreement for participation in a tourist event